Harnessing Technical and Vocational Education and Training and Entrepreneurship Education to Address Unemployment in Lusaka Province, Zambia - Mubanga, Philip; Hock, Oo Yu; Asif, Mahbub Karim; Zulkifli, Senteri; Mulenga, Innocent Mutale; Preckler, Miriam (Scientific Research Publishing, 2019)
The aim of this study was to highlight how a combination of TVET and entrepreneurship education can be harnessed to address the problem of unemployment as well as underutilisation of human resources, in Lusaka Province, Zambia, to foster sustainable social economic development. A questionnaire was administered to TVET students. A representative sample of 480 respondents was targeted. Interview respondents included TVET instructors, TVET administrators, TVET government officers, Industry experts and parents of TVET learners. The sample was proportionately shared among the eight districts in Lusaka province. The study was conducted from April 2018 to March 2019. This was a mixed methods research. Quantitative data was analysed using Statistical Package for Social Sciences (SPSS) and qualitative data through thematic approach. The findings indicated that unemployment as well as underutilisation of human resources can be addressed by tapping into the entrepreneurial ambitions of TVET Learners; encouraging, enticing and appealing to students by asking them to consider entrepreneurship as a vocation or career pathway; offering entrepreneurship education to TVET learners; sensitisation and robust rollout of TVET and entrepreneurship education national wide through policy directives; and, developing appropriate curriculum to support the awareness and recognition that TVET learners that acquire entrepreneurship knowledge and skills are potential productive human resource for different industry sectors to drive sustainable economic development.